2001
DOI: 10.1017/s1352465801001102
|View full text |Cite
|
Sign up to set email alerts
|

Selective Memory Bias in Women With Bulimia Nervosa and Women With Depression

Abstract: Memory bias for weight and shape, and for food related words, was investigated in women with bulimia nervosa (12), women with depression (12) and female nonclinical controls (18). The aim of this study was to investigate whether women with bulimia nervosa demonstrate memory biases congruent with their primary concerns. Participants listened to target and control words. They performed a self-referent encoding task and recall memory was assessed. The results indicated that women with bulimia nervosa demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 19 publications
1
40
2
Order By: Relevance
“…In general, this work suggests that body dissatisfaction is at least as strongly associated with MDD as with BN (Joiner, Schmidt, & Wonderlich, 1997;Joiner, Wonderlich, Metalsky, & Schmidt, 1995;but see, Hurley, Palmer, & Stretch, 1990). However, there is evidence that other specific aspects of disordered eating, including negative assumptions (i.e., thoughts and beliefs) about weight, shape, and eating and selective memory bias for weight and shape-related words, distinguish depressed women from those with eating disorders (Cooper & Hunt, 1998;Hunt & Cooper, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In general, this work suggests that body dissatisfaction is at least as strongly associated with MDD as with BN (Joiner, Schmidt, & Wonderlich, 1997;Joiner, Wonderlich, Metalsky, & Schmidt, 1995;but see, Hurley, Palmer, & Stretch, 1990). However, there is evidence that other specific aspects of disordered eating, including negative assumptions (i.e., thoughts and beliefs) about weight, shape, and eating and selective memory bias for weight and shape-related words, distinguish depressed women from those with eating disorders (Cooper & Hunt, 1998;Hunt & Cooper, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mathews, Mogg, May, & Eysenck, 1989). Previous research has found support for an explicit memory bias in eating-disordered individuals for eating disorder-relevant words (Hermans, Pieters, & Eelen, 1998;Hunt & Cooper, 2001;King, Polivy, & Herman, 1991;Sebastian, Williamson, & Blouin, 1996 Cognitive Behaviour Therapy Vol 37, No 3, pp. 135-145, 2008 bias (Baker, Williamson, & Sylve, 1995;King et al, 1991;Watkins, Martin, Muller, & Day, 1995), whereas others have only found partial (Israeli & Stewart, 2001) or no (Sebastian et al, 1996) support for such effects.…”
mentioning
confidence: 99%
“…Studies using paradigms such as the cued and free recall task and the directed forgetting paradigm indicate that EDs show specific explicit ED-related memory biases: EDs show a memory bias for food-, weight-, and shape-related words and not for general emotional words (Hermans et al 1998;Hunt and Cooper 2001;King et al 1991;Sebastian et al 1996;Suslow et al 2004). It was also found that the memory bias for high-caloric foods was independent of food deprivation in AN participants but not in BN participants (Hunt and Cooper 2001;Pietrowsky et al 2002;Suslow et al 2004). …”
Section: Explicit Memory Biasmentioning
confidence: 96%
“…Research has found convincing support for the existence of an explicit memory bias in ED patients, but data for an implicit memory bias are equivocal (Hermans et al 1998;Hunt and Cooper 2001;King et al 1991;Sebastian et al 1996;Pietrowsky et al 2002). Studies using paradigms such as the cued and free recall task and the directed forgetting paradigm indicate that EDs show specific explicit ED-related memory biases: EDs show a memory bias for food-, weight-, and shape-related words and not for general emotional words (Hermans et al 1998;Hunt and Cooper 2001;King et al 1991;Sebastian et al 1996;Suslow et al 2004).…”
Section: Explicit Memory Biasmentioning
confidence: 99%